The Effect of Return on Assets, Debt to Equity Ratio, and Net Profit Margin on Stock Prices (An Empirical Study of Telecommunications Companies Listed on the IDX from 2020 to 2024) - Fitri Astuti; Ika Rediyana (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on stock prices of telecommunications companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The method used in this study was multiple linear regression analysis with secondary data obtained from annual financial reports. The results show that ROA has a positive and significant effect on stock prices, with a calculated t-value of 2.156 and a significance level of 0.036. Meanwhile, DER does not have a significant effect on stock prices, as evidenced by a calculated t-value of -1.096 and a significance level of 0.278. On the other hand, NPM showed a significant positive effect with a calculated t-value of 5.325 and a significance level of 0.000. Simultaneously, these three independent variables significantly influenced stock prices, with a calculated F-value of 12.303 and a significance level of 0.000. The coefficient of determination test found that the independent variables explained 37.7% of the stock price variation, with the remainder influenced by other factors. This research is expected to provide useful insights and information for investors and stakeholders in making investment decisions in the telecommunications sector.